FOCAD/miR-491-5p, downregulated by EGR1, function as tumor suppressor by inhibiting the proliferation and migration of gastric cancer cells - Sun, Ruifang; Liu, Zhigang; Lv, Yun; Yang, Yanqi; Yang, Yang; Xiang, Yu; Jiang, Qiuyu; Zhao, Chang'an; Lv, Moqi; Zhang, Jian; Zhang, Juan; Ding, Caixia; et al. (Progress in biophysics and molecular biology, 2022)
Gastric cancer is a common malignant tumor in China; however, its carcinogenesis remains unknown. Focadhesin (FOCAD) is a tumor suppressor gene in gliomas, its expression, role, and mechanism in gastric cancer have not been defined. The aim of the present study was to explore the expression pattern of FOCAD in human normal tissues and cancer tissues and elucidate the role and regulatory mechanism of Early Growth Response 1 (EGR1) in FOCAD and its intron, miR-491-5p, in gastric cancer. Immuno histochemical staining revealed that FOCAD is widely and highly expressed in normal gastric mucosa, but is absent in gastric cancer tissue. Based on an association analysis FOCAD expression was found to be negatively associated with lymph node metastasis (P = 0.004); higher FOCAD levels were associated with longer survival in patients with gastric cancer (P = 0.001). MTT, colony, Transwell chamber, and flow cytometry assays revealed that siFOCAD promoted cell proliferation, growth, and migration, and inhibited apoptosis. Furthermore, bioinformatic analysis, Fluorescence reporter gene and chromatin immunoprecipitation analyses confirmed that EGR1 binds to the promoter and negatively regulates FOCAD and miR-491-5p at the transcriptional level. The overexpression of EGR1 was also found to promote cell proliferation, growth, and migration, and inhibit apoptosis. Overall, FOCAD is specifically overexpressed in the gastric mucosa and is significantly downregulated in gastric cancer. To our knowledge, this is the first study to demonstrate that FOCAD is a tumor suppressor, higher FOCAD levels might be a better prognostic marker of gastric cancer, and FOCAD/miR-491-5p may be negatively regulated by EGR1.